The usage of dual-layer remote phosphor configurations in enhancing color quality and luminous flux of WLEDs - Thuc Minh Bui; Phan Xuan Le; Dinh Hoang Bach; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2019)
Among conformal phosphor structure, in-cup phosphor structure, and remote phosphor structure, while in term of attaining the highest luminous flux, remote phosphor structure is the most ideal one, it seems to be that this structure results in the lowest-quality of color. Therefore, it is necessary in conducting experiments to surmount this disadvantage and make a possibility in enhancing the color quality of WLEDs with remote phosphor structure. In this research, with the ability of advancing the color rendering index (CRI) and color quality (CQS) for WLEDs, a dual-layer remote phosphor structure was considered as a suggestion. The experiments in this study used three kinds of WLEDs with the similar structures but different color temperatures varying at 5600 K, 7000 K, and 8500 K. The objectives of this paper is proposing a solution to obtain the highest color quality by placing a yellow-green emitting SrBaSiO4:Eu2+ phosphor layer or a red-emitting SrwFxByOz:Eu2+,Sm2+ phosphor layer on the YAG:Ce3+ phosphor layer and then choosing the most appropriate value of SrwFxByOz:Eu2+,Sm2+ concentration. The experimental results which are satisfied expectations of researchers indicated that SrwFxByOz:Eu2+,Sm2+ has enforced its role in managing to raise the CRI and CQS. Particularly, the greater concentration of SrwFxByOz:Eu2+,Sm2+ leads to the higher the CRI and CQS, since the red light component in WLEDs increased. Besides, the quality of luminous flux is in a tight connection with the SrBaSiO4:Eu2+ phosphor layer. Whereas, according to the Mie scattering theory and the Lambert-Beer law, if the concentration of SrwFxByOz:Eu2+,Sm2+ and SrBaSiO4:Eu2+ becomes redundant, the luminous flux and color quality will take a deep dive. Briefly, the results from this article has largely contributed to fabricating high-quality WLEDs.